Respiratory Diseases 2012
DOI: 10.5772/31036
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Defences of the Lung: Comparative Perspectives

Abstract: 'Our lungs are highly complex organs that are exquisitely specialized for gas exchange and host defense.' Rawlins (2010) 1. Introduction General considerationsThe most important function of the lung is to acquire molecular oxygen and eliminate carbon dioxide. Except probably for the gastrointestinal system, no other organ in the body interacts with the external environment as constantly and as intimately as the respiratory system. For example, during a 24 hour period, at rest, the human lung is ventilated ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 314 publications
(335 reference statements)
0
9
0
Order By: Relevance
“…Although the interpretation is supported by this study, the conclusion reached (by Ibe et al 59 ) in the investigation was not merited by the simple data adduced. For both C. gambianus and C. foxi, the numerous pulmonary goblet cells and alveolar macrophages should constitute an important part of the pulmonary defense system 124,135,136 : the air in the burrows is presumably highly polluted and loaded with pathogens and particulates. Interestingly, a double blood capillary arrangement was observed in some parts of the interalveolar septa of the lung of C. foxi but not in those of C. gambianus.…”
Section: Discussionmentioning
confidence: 99%
“…Although the interpretation is supported by this study, the conclusion reached (by Ibe et al 59 ) in the investigation was not merited by the simple data adduced. For both C. gambianus and C. foxi, the numerous pulmonary goblet cells and alveolar macrophages should constitute an important part of the pulmonary defense system 124,135,136 : the air in the burrows is presumably highly polluted and loaded with pathogens and particulates. Interestingly, a double blood capillary arrangement was observed in some parts of the interalveolar septa of the lung of C. foxi but not in those of C. gambianus.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytes include the polymorphonuclear neutrophils and monocyte/macrophage cells that play an important role in host defence (Brain, ; Djaldetti et al, ; Nicod, ; Maina, ; Wynn, Chawla & Pollard, ). Functional inadequacies in these cells predispose an animal to attack by microbial and viral agents or particulate injury.…”
Section: Cellular Defences Of the Avian Respiratory Systemmentioning
confidence: 99%
“…It shows that the respiratory system of birds has a considerable range of highly specialised cellular defences, including tissuebased phagocytic cells which are exceptionally adept at destroying injurious agents and are mobilised from other sources and rapidly transferred to the epithelial surface where they confer additional protection (Toth & Siegel, 1993). As argued by Nganpiep & Maina (2002a,b), Maina (2002aMaina ( , 2005Maina ( , 2012 and Kiama et al (2008), the high morbidities and mortalities that characterise disease outbreaks in poultry can largely be attributed to factors such as the intense genetic manipulation that birds have undergone during their domestication, intensive genetic breeding practices for rapid weight gain and plentiful egg production, and possibly most importantly the stressful environmental conditions and severe husbandry practices by which poultry production occurs.…”
Section: Defences Of the Avian Lungmentioning
confidence: 96%
“…1E,F) leads to complicated air-flow processes that importantly should determine where, how and to what extent inhaled pathogens and particulates are deposited. While well-structured comparative investigations of the relative susceptibilities between mammalian and avian respiratory systems have not been performed, Brown et al (1997), Fedde (1998) and Maina (2002cMaina ( ,a, 2012 suggested that the intricate arrangement of the airways of the avian lung (Fig. 1C,D), the circuitous path followed by the inhaled air (Fig.…”
Section: Functional Efficiency Of the Avian Respiratory Systemmentioning
confidence: 99%
See 1 more Smart Citation